2020
DOI: 10.1155/2020/6375876
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiome Perturbation in Fatigue Induced by Repeated Stress from Chemoradiotherapy: A Proof of Concept Study

Abstract: Objectives. The objectives of this proof of concept study were to (a) examine the temporal changes in fatigue and diversity of the gut microbiome over the course of chemoradiotherapy (CRT) in adults with rectal cancers; (b) investigate whether there are differences in diversity of the gut microbiome between fatigued and nonfatigued participants at the middle and at the end of CRT; and (c) investigate whether there are differences in the relative abundance of fecal microbiota at the phylum and genus levels betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 51 publications
2
26
1
Order By: Relevance
“…Our LDA analyses, however, revealed that before-treatment participants with co-occurring symptoms were enriched in microbes classified to the genus Bacteroides . This finding is in line with our previous work showing higher relative abundances of Bacteroides in the stool of fatigued participants undergoing CRT (Gonzalez-Mercado et al, 2020). Bacteroides , including B. fragilis , plays an important role in systemic inflammation and neurodegeneration processes (Zhao & Lukiw, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our LDA analyses, however, revealed that before-treatment participants with co-occurring symptoms were enriched in microbes classified to the genus Bacteroides . This finding is in line with our previous work showing higher relative abundances of Bacteroides in the stool of fatigued participants undergoing CRT (Gonzalez-Mercado et al, 2020). Bacteroides , including B. fragilis , plays an important role in systemic inflammation and neurodegeneration processes (Zhao & Lukiw, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Because of the small sample sizes, our results are exploratory in nature and should be interpreted with caution. Nonetheless, this proof-of-concept pilot study builds on prior evidence from our group that CRT-induced comorbidities/symptoms may be associated with gut-microbial dysbiosis (Gonzalez-Mercado et al, 2020; Gonzalez-Mercado et al, 2019). In the present study, we compared the severity of fatigue, sleep disturbance, and depression scores before and at the end of CRT between participants who developed co-occurring symptoms by the end of CRT ( n = 24) and those who developed no symptom ( n = 7).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Multiple studies have shown that the intestinal microbiome of cancer patients is different from that of patients without cancer. In addition, gut microbial dysbiosis prior to radiation therapy may predict fatigue in cancer patients 9 , and chemoradiotherapy can influence colorectal cancer patients’ intestinal microbiome composition and contribute to fatigue 10 .…”
Section: Introductionmentioning
confidence: 99%